An elite endurance athlete's recovery from underperformance aided by a multidisciplinary sport science support team - Gustafsson, H.; Holmberg, H. C.; Hassmen, P. (European Journal of Sport Science, 2008)
Overload training resulting in an overreached state is common in elite sports, and if undetected can develop into an overtraining syndrome. This risk is accentuated by the lack of reliable measures of overreaching. Coaches and scientists therefore have to use a combination of tests in the monitoring process. This article presents a case study of the recovery from underperformance of a young elite endurance athlete and the work of a multidisciplinary sport science support team. When it was determined that the athlete's performance had deteriorated, and that this was due solely to the stress of training, training load was radically reduced for a period of 14 days. A combination of physiological, biochemical, and psychological measurements were then used to monitor the recovery process. The purpose of this article is to describe how coaches and sport science teams can help in monitoring training and recovery in practical settings, allowing detection of the early signs of overreaching before a more serious overtraining syndrome develops.